MAPPACCI AS A MEDIUM OF COMMUNITY MESSAGES IN BONE REGENCY - Nur, Emilsyah; Pala, Rukman (Kementerian Pendidikan dan Kebudayaan, 2020)
This study aims to find out one of the traditional series of Bugis marriage, namely mappacci as a medium of community messages in Bone Regency. Research method applied is qualitative research and data collection techniques are in the form of interview, observation, and library study. The result shows that the meanings contained in the process of mappacci are a form of hope and pray for the welfare and happiness of the bride and groom in a summarized word from nine equipment, namely pillow, silk sarong, jackfruit leaves, banana shoots, pacci leaves, rice, candle, pacci holders, brown sugar, and coconut. The Bugis-Bone community maintains their culture from their ancestor and it is hoped that the young generations can preserve the culture. The tradition of culture in Bugis traditional marriage ceremony in Bone Regency contains a life message values and meanings with a goodness. As one of the cultural heritages of archipelago, it is a duty of young generations to care for and preserve the Bugis culture by respecting and appreciating it, maintaining and filtering it from the outside cultures, and growing love to local culture in early ages.